Homogeneity or interculturality in foreign language pre-service teachers’ education: a reflection on Education Act 02041 - Bertha Ramos-Holguín (Voces y Silencios: Revista Latinoamericana de Educación)
As part of an educational improvement policy, the Colombian Ministry of Education has issued an education law that establishes specific characteristics that teaching programs in Colombia must meet in order to be certified by the government. The primary objective of this article is to show how, by following those features, foreign language pre-service teachers’ education perpetuates homogenization instead of interculturality. The rules stated by the Ministry of Education erase the critical and democratic characteristics teaching programs should have in order to be open spaces for diversity. This article, then, is an attempt to rethink pre-service teachers’ education based on an intercultural perspective that accounts for cultural diversity.